Factors associated with Open Defecation Free (ODF) status among rural communities: A cross-sectional study - Yulis Marita; Eko Heryanto (Lentera Perawat, 2025)
Background: Open defecation remains a persistent public health challenge in many rural communities, particularly where behavioral, socioeconomic, and environmental barriers limit the adoption of safe sanitation practices. Despite national efforts to promote Community-Led Total Sanitation (CLTS), several villages in Indonesia—including Bangun Harjo—continue to experience gaps in Open Defecation Free (ODF) achievement. Objective: This study aimed to examine the factors associated with ODF status among households in a rural Indonesian community, focusing on knowledge, income, environmental proximity to rivers, and family support. Methods: A cross-sectional study was conducted among 232 household heads selected through proportional random sampling. Data were collected using a structured questionnaire and analyzed using univariate and chi-square bivariate tests to determine associations between independent variables and ODF status. Results: The findings showed that 63.8% of households had achieved ODF status, while 36.2% continued practicing open defecation. Knowledge demonstrated a significant association with ODF status, where households with good knowledge were more likely to adopt safe sanitation practices (p < 0.001). Income was also significantly associated with ODF status, with higher-income households more capable of constructing and maintaining latrines (p < 0.001). Environmental distance showed strong influence, as households near rivers were more likely to practice open defecation (p < 0.001). Family support similarly contributed to increased ODF achievement, indicating the importance of household dynamics in sustaining sanitation behavior (p < 0.001). Conclusion: ODF achievement in rural settings is shaped by interconnected factors, including knowledge levels, economic capacity, environmental accessibility, and family support. These determinants highlight the need for integrated and context-specific sanitation strategies.